Debt-Sensitive Majority Rules - Oliver Grimm; Johannes Becker; Hans Gersbach (Verein für Socialpolitik, 2010)
We examine debt-sensitive majority rules. According to such a rule, the higher a planned public debt, the higher the necessary parliamentary majority to approve it. In a two-period model, we compare debt-sensitive majority rules with the simple majority rule when individuals differ regarding their benefits from public good provision. We establish the existence of Condorcet winners under debt-sensitive majority rules and derive their properties. We find that equilibrium debt-levels are lower under the debt-sensitive majority rule if preferences regarding public goods are sufficiently heterogeneous and if the impact of debt on future public good provision is sufficiently strong. We illustrate how debt-sensitive majority rules act as political stabilizers of negative macroeconomic shocks.
Keywords: H63; D72; E61; 330; fiscal policy; public debt; public goods; voting; simple majority rule; debt-sensitive majority rule; debt restriction